An Antarctic research station as a source of brominated and perfluorinated persistent organic pollutants to the local environment - S Wild; D McLagan; M Schlabach; R Bossi; D Hawker; R Cropp; CK King; JS Stark; Julie Mondon; SB Nash (2015)
This study investigated the role of a permanently manned Australian Antarctic research station (Casey Station) as a source of contemporary persistent organic pollutants (POPs) to the local environment. Polybrominated diphenyl ethers (PBDEs) and poly- and perfluoroalkylated substances (PFASs) were found in indoor dust and treated wastewater effluent of the station. PBDE (e.g., BDE-209 26-820 ng g(-1) dry weight (dw)) and PFAS levels (e.g., PFOS 3.8-2400 ng g(-1) (dw)) in dust were consistent with those previously reported in homes and offices from Australia, reflecting consumer products and materials of the host nation. The levels of PBDEs and PFASs in wastewater (e.g., BDE-209 71-400 ng L(-1)) were in the upper range of concentrations reported for secondary treatment plants in other parts of the world. The chemical profiles of some PFAS samples were, however, different from domestic profiles. Dispersal of chemicals into the immediate marine and terrestrial environments was investigated by analysis of abiotic and biotic matrices. Analytes showed decreasing concentrations with increasing distance from the station. This study provides the first evidence of PFAS input to Polar regions via local research stations and demonstrates the introduction of POPs recently listed under the Stockholm Convention into the Antarctic environment through local human activities.